Concept of fiendship and social network of children in Dao Elementaru Central School, Capiz. - Apolinario, Charmaine Joy Barrientos; Tuto, Agnes Jill. (2004.)
This is a descriptive study of children's concept of friendship and their social network. this sought to know the concept of children about friendship and how they form their social network. Likewise, it also examined the kind of ralationship among children., A total of sixty (60) participants were randomly chosen in the study. Out of the total participants, 29 were males and 31 females. The participants were obtained from Dao Central School Capiz using fishbowl method of simple random sampling. In gathering data, an open-ended questionnaire, furman Friendship questionnaire and the Kite Network were used. Percentage, frequency distribution and average mean were used as tools of analysis. Friendship of children is determined on the basis of good attitude that friends have to each other. The important of gender and age were emphasized in viewing friendship and in forming children's social network. School serves as a venue to where children find their friends, also children gained friends through texting. In children's social network, children were closely interconnected to same age and gender friends.
Research Project (Undergraduate, Bachelor of Arts in Psychology) College of Arts and Sciences, UP Visayas, Miagao, Iloilo
Keywords: Children -- Dao Elementary School, Capiz; Friendship, concept of; Children -- Social network